2021
DOI: 10.3390/app11041809
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Ranges and TestBeds for Education, Training, and Research

Abstract: In recent years, there has been a growing demand for cybersecurity experts, and, according to predictions, this demand will continue to increase. Cyber Ranges can fill this gap by combining hands-on experience with educational courses, and conducting cybersecurity competitions. In this paper, we conduct a systematic survey of ten Cyber Ranges that were developed in the last decade, with a structured interview. The purpose of the interview is to find details about essential components, and especially the tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…The theory is rarely utilised to explain what factors are affecting users' compliance with security policies or even provide empirical evidence from their actual application. In general, it is suggested that training programmes should make use of methods and contents that are actively engaging trainees and motivate them to undergo systematic cognitive processing of the taught information [17,20]. Apart from modern technological tools (e.g., simulation, serious games), the continuous communication of the trainer with the learners is vital to improving users' security compliance [12,17,20].…”
Section: Adopting Training In the Workplacementioning
confidence: 99%
See 4 more Smart Citations
“…The theory is rarely utilised to explain what factors are affecting users' compliance with security policies or even provide empirical evidence from their actual application. In general, it is suggested that training programmes should make use of methods and contents that are actively engaging trainees and motivate them to undergo systematic cognitive processing of the taught information [17,20]. Apart from modern technological tools (e.g., simulation, serious games), the continuous communication of the trainer with the learners is vital to improving users' security compliance [12,17,20].…”
Section: Adopting Training In the Workplacementioning
confidence: 99%
“…A simplified illustration of the training transfer model is depicted in Figure 1. However, it is estimated that around 10-40% of all training experiences will be transferred to the workplace [7,17,18]. Moreover, as time passes from the completion of the training programme, employees usually becoming less motivated to retain the new operational behaviours (e.g., after one year).…”
Section: Adopting Training In the Workplacementioning
confidence: 99%
See 3 more Smart Citations